PENGARUH KUALITAS AUDIT, TRANSISI ENERGI, DAN KOMITE AUDIT TERHADAP UKURAN PERUSAHAAN DENGAN ESG DISCLOSURE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Aldino Rafael Yusup; Nera Marinda Machdar (Jurnal Ilmiah Akuntansi, 2026)
This study examines the influence of audit quality, energy transition, and audit committee on firm size, as well as the moderating role of ESG disclosure in manufacturing companies listed on the Indonesia Stock Exchange. A quantitative approach was applied using secondary data obtained from annual reports and sustainability reports for the 2020–2024 period. The data were analyzed using multiple linear regression and moderated regression analysis (MRA). The results show that audit quality, energy transition, and audit committee each have a significant positive effect on firm size. Furthermore, ESG disclosure strengthens these relationships by enhancing the credibility and transparency of corporate reporting. These findings provide empirical evidence of how governance mechanisms and sustainability practices jointly support firm development, offering practical implications for improving disclosure strategies and strengthening corporate accountability.